Sejarah Kesultanan Demak: Dari Raden Fatah Sampai Arya Penangsang - Zuliani Putri (IAIN Syekh Nurjati Cirebon, 2021)
Abstract: The Sultanate of Demak was founded in the late 15th century and was the first Islamic sultanate on the island of Java, after the Kediri kingdom attacked and destroyed the capital of the Majapahit kingdom in Trowulan by 1474. The Sultanate of Demak was led by a son from Brawijaya V with a daughter from Campa, namely Raden Fatah. This paper will discuss the formation of the Demak Sultanate until its collapse. The purpose of this research is to determine the process of the formation of the Sultanate of Demak until the process of its collapse. This article uses the library research method. Library research is a data collection technique by reviewing books, documents, notes, and various reports related to the problem to be solved. Demak is the first Islamic sultanate on the island of Java. Demak is the area given by Brawijaya V to his son Raden Fatah. Since Raden Fatah became the ruler, Demak also had a large port, which became a means of transportation for fishermen and trade, until this Sultanate became the first Islamic sultanate in Java. The Sultanate of Demak was founded by Raden Fatah in 1478. Keywords: Sultanate of Demak, Raden Fatah, Islam